KENDALA IMPLEMENTASI GERAKAN LITERASI SEKOLAH (GLS) DI SD NEGERI 8 BANJAR - seriantini, nengah (ACARYA PUSTAKA, 2024)
This research focuses on (1) What are the obstacles faced by SD Negeri 8 Banjar in the implementation of the School Literacy Movement (GLS). (2) What efforts are made in overcoming obstacles in the implementation of the School Literacy Movement (GLS). The research method used is a qualitative descriptive research method with a purposive sampling technique for collecting informants. This research took place in the Library of SD Negeri 8 Banjar. Data collection in this study uses observation techniques, interviews, and document studies. The result of this study is that SD Negeri 8 Banjar has not succeeded in implementing the School Literacy Movement (GLS) program until now.Before the Covid-19 pandemic, SD Negeri 8 Banjar had implemented the program, but it was only running temporarily and not optimally, until now the School Literacy Movement (GLS) program has not implemented it again. SD Negeri 8 Banjar faces various obstacles that can hinder the optimal implementation of the School Literacy Movement (GLS) program. These obstacles include a lack of understanding and commitment from several parties, both teachers, students, and library staff, not only that the implementation time is also an inhibiting factor for the School Literacy Movement (GLS) program, this is often an obstacle in creating a sustainable literacy culture.